2019
DOI: 10.1152/ajprenal.00215.2019
|View full text |Cite
|
Sign up to set email alerts
|

High glucose reduces expression of podocin in cultured human podocytes by stimulating TRPC6

Abstract: The transient receptor potential canonical 6 (TRPC6) channel and podocin are colocalized in the glomerular slit diaphragm as an important complex to maintain podocyte function. Gain of TRPC6 function and loss of podocin function induce podocyte injury. We have previously shown that high glucose induces apoptosis of podocytes by activating TRPC6; however, whether the activated TRPC6 can alter podocin expression remains unknown. Western blot analysis and confocal microscopy were used to examine both expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…However LMX1B mutations are causative in the syndromic disease nail–patella syndrome characterized by hypoplastic nails and patella, skeletal deformities and varying degrees of nephropathy [ 89 , 90 , 95 ]. The underlying pathophysiology caused by mutations affecting podocin relates to impaired nephrin signaling due to the inability of nephrin to associate with lipid rafts as well as podocin’s effects on TRPC6 [ 52 , 82 , 96 , 97 , 98 ].…”
Section: Structural Regulation Of Actin Dynamics In Podocytesmentioning
confidence: 99%
“…However LMX1B mutations are causative in the syndromic disease nail–patella syndrome characterized by hypoplastic nails and patella, skeletal deformities and varying degrees of nephropathy [ 89 , 90 , 95 ]. The underlying pathophysiology caused by mutations affecting podocin relates to impaired nephrin signaling due to the inability of nephrin to associate with lipid rafts as well as podocin’s effects on TRPC6 [ 52 , 82 , 96 , 97 , 98 ].…”
Section: Structural Regulation Of Actin Dynamics In Podocytesmentioning
confidence: 99%
“…Several studies have indicated that mice treated with morphine develop podocyte injuries and increased urinary albumin excretion (Lan et al, 2013) as well as podocyte foot process effacement accompanied by the loss of GFB integrity (Weber et al, 2012). Calcium signaling plays an essential role in podocyte pathophysiology (Dryer et al, 2019;Hall et al, 2019;Lu et al, 2019). TRPC proteins, belonging to the larger TRP superfamily, form Ca 2+ -permeable channels and play an important role in the pathogenesis of renal and cardiovascular diseases (Abramowitz & Birnbaumer, 2009;Spires et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this possibility, podocyte-specific overexpression of TRPC6 in vivo promotes proteinuria and modest glomerulosclerosis [63]. Since these initial observations, enhanced expression of TRPC6 has been demonstrated in other kidney diseases including rodent models of diabetic nephropathy [61,[64][65][66][67][68][69], nephrotoxic serum nephritis [70,71], rodent models of FSGS [61,64,[72][73][74], and ureteral obstruction [75,76]. Thus, increased expression of TRPC6 may be a common finding in a broad range of pathologic conditions affecting the kidney.…”
Section: Trpc Family Members In Glomerular Diseases: Mechanisms Of Rementioning
confidence: 99%
“…In this regard, podocyte damage and dysfunction are early features of diabetic kidney disease, eventually leading to a decrease in podocyte number and, in turn, disease progression [22,23]. In support of a role for TRPC6 in diabetic nephropathy, glomerular expression of TRPC6 is upregulated in kidneys from rodent models of diabetes [61,[64][65][66][67]69], and knockdown of TRPC6 in cultured podocytes both inhibits hyperglycemia-induced apoptosis [90,131] and preserves podocin expression [69]. In addition, several studies suggest that inhibitors of TRPC6 transcription [64,65,72,77] ameliorate albuminuria and the histologic features of diabetic kidney disease in rodent models [64,66,132].…”
Section: Targeting Trpc Family Members To Treat Diabetic Nephropathymentioning
confidence: 99%